Features of the Investor State Dispute Settlement (ISDS) Provisions under Bilateral Investment Treaties (BITs) of Bangladesh: An Overview (Dhaka University Law Journal, 2021)
Abstract not availableDhaka University Law Journal, Vol. 31, 2020 P.85-103